The Role of Aisyiyah in Women’s Empowerment in Bandar Lampung City in 1971-2000 - Muntamah, Siti; Basyori, Ahmad; Hasanah, Uswatun; Hamid, Abd Rahman; Setiawan, Agus Mahfudin (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This study aims to examine the role of Aisyiyah in women's empowerment in Bandar Lampung City from 1971-2000. The method used in this study is the historical method, which includes the stages of heuristics (source collection), source criticism, interpretation, and historiography. The study results show that Aisyiyah plays an active role in women's empowerment through various programs. In the field of education, Aisyiyah established kindergartens (TK) as part of efforts to educate the younger generation. In the social aspect, this organization initiated the Aisyiyah Foster Children program, the "Aisyiyah Building the People with Social Justice" training, and the Aisyiyah Sakinah Family program. Meanwhile, in the economic sector, Aisyiyah developed the Aisyiyah Family Economic Development (BUEKA) to increase women's financial independence. In the health sector, Aisyiyah carries out Maternal Health and Child Survival (KIKHA) training as well as infectious disease and AIDS prevention programs in Bandar Lampung. This research reveals that the success of Aisyiyah not only lies in innovation in da'wah methods but also in its ability to adapt to social dynamics without leaving Islamic values. This finding makes an important contribution to understanding Islamic da'wah strategies at the local level as well as the strategic role of Aisyiyah in women's empowerment.